Effects of multiple dimensions of bacterial diversity on functioning, stability and multifunctionality. Issue 10 (15th September 2016) - Roger, Fabian; Bertilsson, Stefan; Langenheder, Silke; Osman, Omneya Ahmed; Gamfeldt, Lars
Abstract: Bacteria are essential for many ecosystem services but our understanding of factors controlling their functioning is incomplete. While biodiversity has been identified as an important driver of ecosystem processes in macrobiotic communities, we know much less about bacterial communities. Due to the high diversity of bacterial communities, high functional redundancy is commonly proposed as explanation for a lack of clear effects of diversity. The generality of this claim has, however, been questioned. We present the results of an outdoor dilution‐to‐extinction experiment with four lake bacterial communities. The consequences of changes in bacterial diversity in terms of effective number of species, phylogenetic diversity, and functional diversity were studied for (1) bacterial abundance, (2) temporal stability of abundance, (3) nitrogen concentration, and (4) multifunctionality. We observed a richness gradient ranging from 15 to 280 operational taxonomic units (OTUs). Individual relationships between diversity and functioning ranged from negative to positive depending on lake, diversity dimension, and aspect of functioning. Only between phylogenetic diversity and abundance did we find a statistically consistent positive relationship across lakes. A literature review of 24 peer‐reviewed studies that used dilution‐to‐extinction to manipulate bacterial diversity corroborated our findings: about 25% found positive relationships. Combined, these results suggest that bacteria‐driven community functioning is relatively resistant to reductions in diversity.